HUBUNGAN ANTARA HARDINESS DENGAN ADAPTABILITAS KARIR PADA MAHASISWA FAKULTAS VOKASI PELAYARAN DI UNIVERSITAS HANG TUAH SURABAYA - Choirum Marodatun Nisa; Wiwik Sulistiani; Puri Aquarisnawati (Fakultas Psikologi Universitas Hang Tuah, 2022)
The purpose of this study was to determine the relationship between hardiness and career adaptability at the Vocational School at Hang Tuah University, Surabaya. This study uses a quantitative approach to survey methods and uses product moment correlation. Data collection uses a hardiness scale of 15 items and a career adaptability scale of 24 items. The number of subjects in this study were 100 cadets at the Faculty of Vocational Shipping, Hang Tuah University, Surabaya. The sampling technique used non-probability sampling technique. The results showed that there was a positive and significant relationship between hardiness and career adaptability at the Vocational Vocational School at Hang Tuah University, Surabaya.